PENGEMBANGAN EKOWISATA BERBASIS KERAKYATAN DI BANJAR NYUH KUNING, DESA MAS, UBUD - SULISTYAWATI, AGUNG SRI (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
The objective of this study is (1) to identify the potential of Banjar Nyuh Kuning Mas Village, Ubud has to offer as means of attraction in ecotourism which may be accomplished by identifying physical and non physical potential. (2) to develope a community based strategy in ecotourism. The sampling technique used is purposive sampling and accidental sampling. Data collection is accomplished through observatioan, questionaire, focus group discussion and documentation. Data analysis is by qualitative descriptive and SWOT. The result of this study is that Banjar Nyuh Kuning has the potential to be developed as an ecotourism on the basis of physical and non physical grounds. The perception of the community and tourists are in agreement to the developement of ecotourism activity which incorporate local community, nature oriented activity and has the potential to increase their income, thus resulting in a destination for leisure and recreation. There are a few results of alternative strategies such as; development strategies of ecotourism products, development strategies of human resources, development strategies of management and strategies in upgrading security. To make Banjar Nyuh Kuning as an attraction for ecotourism activity which is based on nature then the strategy for development has to be efficient and limited. Further study has to be taken for the marketing aspect and managing ecotourism object to further the developent in a comprehensive manner.
Keywords: development strategy, ecotourism, community based tourism